2019
DOI: 10.1002/chem.201904621
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinylidenaminophosphines: Facile Access to Highly Electron‐Rich Phosphines

Abstract: Electron‐rich tertiary phosphines are valuable species in chemical synthesis. However, their broad application as ligands in catalysis and reagents in stoichiometric reactions is often limited by their costly synthesis. Herein, we report the synthesis and properties of a series of phosphines with 1‐alkylpyridin‐4‐ylidenamino and 1‐alkylpyridin‐2‐ylidenamino substituents that are accessible in a very short and scalable route starting from commercially available aminopyridines and chlorophosphines. The determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
5
40
0
1
Order By: Relevance
“…Note that the determination of the donor strength of 3 using a solid sample of [Ni(CO) 3 ( 3 )] gives an even lower TEP value of 2037.1 cm –1 . It has been observed that the interaction of the basic nitrogen atoms adjacent to the phosphorus atom with acidic CH protons such as those in dichloromethane can increase the TEP value , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the determination of the donor strength of 3 using a solid sample of [Ni(CO) 3 ( 3 )] gives an even lower TEP value of 2037.1 cm –1 . It has been observed that the interaction of the basic nitrogen atoms adjacent to the phosphorus atom with acidic CH protons such as those in dichloromethane can increase the TEP value , …”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the interaction of the basic nitrogen atoms adjacent to the phosphorus atom with acidic CH protons such as those in dichloromethane can increase the TEP value. [15,32] In order to compare the stability of the phosphines towards oxidation with molecular oxygen, phosphines 1a and 3 were exposed to an oxygen atmosphere at room temperature. 31 P NMR analysis of the reaction mixture showed partial decomposition (30 %) of 1a and complete decomposition of 3 after nine hours (see the Supporting Information).…”
Section: Single-crystal X-ray Diffraction (Xrd) Studies Of 1a•hcl Andmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This class of ligands allows for easy tuning of donor and steric capacities by varying substituents on the N-(abundance of amines, including easily accessible imidazol-2-ylidene-and pyridinylide amines), the Pcenter or both. [23][24][25][26][27][28][29] Arylamino groups attenuate the basicity of the P-donor atom through resonance and σ-electron withdrawal, while aliphatic amino groups increase the basicity due to the absence of the π-system. [30] This was idependently demonstrated by Ziółkowski [31] and Woollins, [32] studying the electronic properties of N-pyrrolyl-and N-pyrrolidinyl-phosphines employing v CO of trans-[RhCl(CO)L 2 ], respectively.…”
mentioning
confidence: 99%
“…In terms of weaker reductants, this equationy ields E 1/2 values for 8R of À0.76 Vf or R = F( TEP = 2110.8 cm À1 ), or À1.01 Vf or more synthetically accessible R = O-p-C 6 H 4 CN (TEP = 2092.8 cm À1 ). On the other hand, the recent reports [32][33][34][35][36][37][38] of av ariety of phosphines that are more donating than the classical benchmark PtBu 3 (TEP = 2056.1 cm À1 )p rovide new possibilities for highly reducing derivatives of 8R with pre-dicted redoxp otentials as low as À2.12 Vv s. SCE. (see Table 2).…”
mentioning
confidence: 99%